POLA TIDUR DENGAN TEKANAN DARAH PADA IBU HAMIL TRIMESTER III DI BPM NY. E DESA BENDUNGANJATI KECAMATAN PACET KABUPATEN MOJOKERTO - Zulfa Rufaida; Sri Wardini Puji Lestari; Ika Yuni Susanti (LPPM Sekolah Tinggi Ilmu Kesehatan Majapahit Mojokerto, 2019)
Pregnant women with sleep disorders may have an impact on the fetus. The babies born to depressed mothers from sleep disturbances during pregnancy have less time to sleep. This condition can cause depression and stress that affect the fetus it contains so that mild stress and has increased heart rate. In case of severe stress for a long time will result in the fetus becomes hyperactive. This study aims to determine sleep patterns with blood pressure in pregnant women trimester 3. This research used cross sectional study design. The variables studied were sleep pattern as independent variable and blood pressure as dependent variable. The population is the third trimester pregnant woman in BPM Ny. E Desa Bendunganjati Pacet Mojokerto as many as 30 people. Sampling conducted non Probability Sampling by using sampling saturated / total sampling counted 30 people. Data retrieval by retrieving primary data. The data have been analyzed using Chi-square test with α: 0.05.The results of this study showed that 30 respondents most of the trimester pregnant women had an abnormal sleep pattern of 17 respondents (56.7%), and almost half with normal sleep pattern of 13 respondents (43.3%). Almost all respondents had normal blood pressure as many as 23 respondents (76.7%), and a small percentage of respondents had hypertension as many as 7 respondents (23.3%). Based on chi square test found result 2 cell Frequency of expectation that is <5 then another test that is test kolmogorov smirnov result 0.001 which means <0,05 so there is relation between sleep pattern with blood pressure in pregnant mother trimester 3. Normal sleep patterns are averaged for 8 hours per day, causing normal maternal blood pressure on average about 120/80 mmHg and most expectant maternal sleeping patterns are an average of sleep for 6 hours resulting in a small part of the mother pregnant hypertension with an average blood pressure of 150/100 mmHg. For that pregnant women should really maintain sleep patterns. In the hope of health workers, especially midwives provide counseling and counseling about the importance of good sleep patterns and healthy lifestyle that will provide a good impact on mother and fetus.